[Lužný, Dušan. Nová náboženská hnutí] - Václavík, David (Religio, 1998)
Reviewed works: Lužný, Dušan. Nová náboženská hnutí. 1. vyd. Brno: Masarykova univerzita, 1997. 181 s. Religionistika; sv. 3. ISBN 80-210-1645-0.